‘Known by God’: The Meaning and Value of a Neglected Biblical Concept - Rosner, Brian S. (Tyndale bulletin, 2008)
Despite the fact that being known by God is a critical concept in biblical theology it is sorely neglected in biblical exegesis and theology. This introductory article seeks to revive interest in the doctrine by reflecting on its definition and by considering its pastoral function in the Bible and in early Jewish texts. It argues that being known by God is roughly equivalent to three related notions: belonging to God, being loved or chosen by God, and being a child or son of God. With respect to the use to which it is put in the relevant texts, whereas not being known by God adds severity to dire warnings, being known by God promotes humility and supplies comfort and security. The implications of a biblical doctrine of being known by God for Christology, Anthropology, and Ethics are also briefly considered.